Penerapan Metode Material Requirement Planning Pada Sistem Informasi Persediaan Bahan Baku Pupuk Dolomite Dan Pupuk Calsium Di CV. Sambong Margo Utomo - Subagio, Agus; Mashuri, Chamdan (Inovate, 2023)
Fertilizer production activities require planning an adequate supply of raw materials to meet production needs so as not to experience shortages and excess stocks of raw materials. This research was conducted in the warehouse CV. Sambong Margo Utomo who experienced problems in the stock of raw material supplies due to the limited storage space they had and the data processing was still manual. The objectives to be achieved in this research are (1) To design an information system for the supply of raw materials for dolomite and calcium fertilizers (2) To build inventory system software using Material Requirement Planning (MRP) (3) To implement Material Requirement Planning (MRP) in planning the need for raw materials for fertilizer in CV. Sambong Margo Utomo. The results of this study, namely the Material Requirement Planning (MRP) method can be applied to an information system for the supply of raw materials for dolomite and calcium fertilizers in CV. Sambong Margo Utomo and testing of raw material inventory planning in January 2018 - December 2018 resulted in the frequency of orders, inventory costs and safety stock for each raw material. Keywords – Information System, Raw Material Inventory, Material Requirement Planning